Connections, concepts and cartographies: re-imagining sustainable education systems through perceptive engagement with children in contemporary education - Laura Barritt (University of Aberdeen, School of Education, 2022)
Concepts of sustainability should underpin education systems across the globe. Yet, strong positivist views have dominated Western knowledge structures for centuries, privileging isolated, quantifiable paradigms over holistic knowledge-making practices as lived and known by alternative groups of peoples and ages. If education systems aid in the shaping of future thinking through the minds that they cultivate in schools (Eisner, 2002), then it is imperative that they address a deeper understanding of how various influences co-construct entangled and distributed ways of knowing and becoming-with-the-world (Haraway, 2016). The role of perceptive engagement with the environment at various levels by children has been highlighted by Ecological Systems Theory (Bronfenbrenner, 1979) and provides a means by which environments cultivate thinking and behaviours. Connection and co-production between different levels of influence (including digital influences) have been recognised by some education reforms such as the CfE in Scotland (2010) and the CfW in Wales (2015; 2022). These reforms have started to engage with the productive nature of such systems, considering how they may intercept and interact at different levels in co-creating the holistic development of children, and therefore the wider ecology of education and learning. Engaging with children as co-creators of learning experience can begin to make visible different relations between environments that co-construct thinking and agency in the world. Through materialising children's engagement with the world through 'relationscapes' (Manning, 2012), we can begin a dialogue that could lead to new ways of understanding the progressive equilibrium by which mind, and life can not only be sustained, but also thrive in a shared future.